A study of gas sensing properties of ZnO nanostructures activated by UV light - Procek, Marcin; Pustelny, Tadeusz (Photonics Letters of Poland, 2015)
In this paper the response of resistance gas sensors is investigated, based on zinc oxide nanostructures to NO2. The research is focused on the influence of ultraviolet light on the operation of such sensors at room temperature. Comparative experiment results are presented and discussed for thermal (200 oC) and UV (LED: λ=390 nm) activation in different carrier gases (air and nitrogen). Full Text: PDF References R.K. Sonker, S.R. Sabhajeet, S. Singh, B.C. Yadav, "Synthesis of ZnO nanopetals and its application as NO2 gas sensor", Mat. Lett. 152, 189 (2015). CrossRef M. Procek, T. Pustelny, A. Stolarczyk, E. Maciak, "Studies of changes in electrical resistance of zinc oxide nanostructures under the influence of variable gaseous environments", Bull. Pol. Acad. Sci. Tech.Sci. 62(4), 635 (2014). CrossRef T. Pustelny et al., "Gas sensors based on nanostructures of semiconductors ZnO and TiO2", Bull. Pol. Acad. Sci. Tech.Sci. 60(4), 853 (2012). CrossRef M.A. Borysiewicz et al., "Sputter deposited ZnO porous films for sensing applications", Mat. Res. Soc. Symp. Proc. 1494, 71 (2013). CrossRef H. Chen, Y. Liu, C. Xie, J. Wu, D. Zeng and Y. Liao, "A comparative study on UV light activated porous TiO2 and ZnO film sensors for gas sensing at room temperature", Cera. Inter. 38, 503 (2012). CrossRef Z. Bielecki et al., "Sensors and Systems for the Detection of Explosive Devices - An Overview", Metrol. Meas. Syst. 19, 3 (2012). CrossRef M. Procek, A. Stolarczyk, T. Pustelny, E. Maciak, "A Study of a QCM Sensor Based on TiO2 Nanostructures for the Detection of NO2 and Explosives Vapours in Air", Sensors 15(4), 9563 (2015). CrossRef J.H. Lee, "Gas sensors using hierarchical and hollow oxide nanostructures: Overview", Sens. Actuators B Chem. 140(1), 319 (2009). CrossRef T. Pustelny et al., "The sensibility of resistance sensor structures with graphene to the action of selected gaseous media", Bull. Pol. Acad. Sci. Tech.Sci. 61(2), 293 (2013). CrossRef S. Derwniak, T. Pustelny, R. Muzyka, G. Konieczny, P. Kałużyński, "The effect of oxidation and reduction processes of graphite on physicochemical properties of graphite oxide and reduced graphene oxide", Phot. Lett. Poland 6(4), 130 (2014). CrossRef A.D. Dobrzańska?Danikiewicz et al., "Resistance changes of carbon nanotubes decorated with platinum nanoparticles in the presence of hydrogen at different and constant concentrations", Phys. Stat. Soli. B, 251(12), 2426 (2014). CrossRef T. Pustelny, J. Ignac-Nowicka, B. Jarzabek, A. Burian, "Optical investigations concerning layered metalphthalocyanine nanostructures affected by NO2", Optica Appl. 34(4), 551 (2004). DirectLink Z.W. Dong, C.F. Zhang, H. Deng, G.J. You, S.X. Qian, "Raman spectra of single micrometer-sized tubular ZnO", Mate. Chem. Phys. 99(1), 160 (2006). CrossRef C.F. Windich Jr., G.J. Exarhos, Ch. Yao, L.Q. Wang, "Raman study of the influence of hydrogen on defects in ZnO", Jour. Appl. Phys. 101, 123711 (2007). CrossRef